Possibilities of the Correction for Combined Pathology of the Esophagus and Gastroduodenal Zone in Children with the Use of Multi-Component Phytopreparation - O.Yu. Belousova; N.V. Pavlenko; E.B. Ganziy; K.V. Voloshin; A.M. Kaafarani (Zaslavsky O.Yu., 2016)
The paper presents the own results of the research on the clinical efficacy and safety of multi-component phytopreparation Gastritol as monotherapy of concomitant functional disorders of the esophagus and stomach in young children and as a part of comprehensive therapy for gastroesophageal reflux disease combined with chronic gastroduodenitis and peptic ulcer disease in older patients. Recommendations are presented on the use of the drug based on the results of its efficacy, safety in different variants of therapy in children of all age groups.